Read & think Italian (McGraw-Hill, 2022)
Read & Think Italian contains more than 115 fascinating articles that reveal the enchanting diversity of Italian culture. Written in Italian, these readings provide insight into many aspects of Italian-speaking life and its traditions, from Lake Como glamor to a Sicilian flower festival, and from Vespa culture in Rome to the development of new customs around the Italian dining Table.